Answer:
The sequence is step 7, 9, 1, 4, 2, 8
Explanation:
They give us a series of steps to organize the operation of the inverse of the function y = (x-4) / (33-x)
they give us 9 steps, which 3 are incorrect since it is only done in 6 steps.
1. The first step is step # 7
It is the exchange of variables, it would be:
x = (y -4) / (33 - y)
2. The second step is step # 9
the denominator (33-y) is multiplied by x, like this:
x * (33 - y) = y -4
3. The third step is step # 1
Multiply the x by 33 - y, like this:
33 * x - x * y = y - 4
4. The fourth step is step # 4
We rearrange the equation:
33 * x + 4 = y + x * y
5. The fifth step is step # 2
We take common factor "and"
33 * x + 4 = y * (1 + x)
6. The sixth and last step is step # 8
We solve for "y", that is, we pass divide (1 + x) and it would be:
y = f ^ -1 (x) = 33 * x + 4 / (1 + x)